Vibration energy harvesting from impulsive excitations via a bistable nonlinear attachment—Experimental study. (15th June 2019) - Chiacchiari, Sandra; Romeo, Francesco; McFarland, D. Michael; Bergman, Lawrence A.; Vakakis, Alexander F.
Highlights: A bistable vibration energy harvester coupled to a hosting structure is proposed. An electromagnetic coupling transducer is used for kinetic energy conversion. The bistability enables to overcome the inefficiency threshold of cubic harvesters. The theoretical model priorly studied is experimentally validated. Harvesting capability over broad ranges of excitation energy level and frequency. Abstract: A bistable nonlinear electromagnetic energy harvester coupled to an impulsively excited primary linear oscillator has been experimentally investigated. The design of the energy harvesting system was guided by a preliminary numerical study, which predicted a favorable dynamic regime for harvesting purposes. The harvesting system consisted of a lightweight permanent magnet, moving within a stationary coil, nonlinearly coupled to a grounded, weakly damped linear oscillator through a prebuckled, bistable slender steel beam which exhibited both cubic nonlinear and negative linear stiffness behaviors in transverse response along its weak axis. This paper provides the results of an experimental investigation, illustrating the capacity of the bistable element to dramatically enhance harvesting efficiency when subjected to broadband, low-amplitude vibration, executing large amplitude oscillations between the two stable equilibrium positions. Single and repeated impulses of varying amplitude applied to the LO are employed as system inputs, and it is shown, both experimentally and through numerical simulations, that robust harvesting efficiency is achieved primarily through periodic cross-well oscillations, particularly at low levels of input energy.